Size-dependent modelling of elastic sandwich beams with prismatic cores. (April 2018) - Reinaldo Goncalves, Bruno; Romanoff, Jani
Abstract: Sandwich panel strips with prismatic cores are modelled using the modified couple stress theory and their elastic size-dependent bending behaviour investigated. Compatibility between the discrete sandwich and continuum beam kinematics is first discussed. A micromechanics-based framework to estimate effective mechanical properties is provided and unit cell models constructed with elementary beam elements to determine the stiffness parameters of various prismatic cores. Numerical studies show that the modified couple stress Timoshenko beam enhances the static deflection predictions of the classical Timoshenko model. A sensitivity measure based on structural ratios is proposed to estimate the influence of size effects in the global beam-level response. The parameters governing size effects in elastic sandwich beams are identified: Face-to-core thickness ratio, core density and topology, vertical corrugation order and set of load and boundary conditions. Size effects are shown more pronounced in low-density cores that rely on corrugation bending as shear-carrying mechanism. Based on the external load, boundary conditions and sensitivity factor, one can assess whether size effects are non-negligible in a given engineering structure.